Pengaruh Kebijakan Deviden, Keputusan Investasi, Struktur Modal dan Profitabilitas Terhadap Nilai Perusahaan pada Perusahaan Perbankan Konvensional yang Terdaftar di BEI Tahun 2022-2025 - Dewi Pramesti, Finadia Alfioneta; Septriana, Ira; Herawati, Ratna; Setyowati, Lilis (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of dividend policy, investment decisions, capital structure, and profitability on firm value in conventional banking companies listed on the Indonesia Stock Exchange during the 2022–2025 period. The research employs a quantitative approach with an associative method, with samples selected through purposive sampling using secondary data from annual financial reports, analyzed using multiple linear regression with the assistance of SPSS, preceded by classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation. The results show that dividend policy and capital structure have no significant effect on firm value, while investment decisions and profitability are proven to have a positive and significant effect on firm value. This indicates that the proportion of dividends distributed and the composition of debt and equity are not yet the main considerations for investors in assessing banking companies, given that such policies are largely shaped by capital-related regulatory requirements. Conversely, investors place greater attention on expected earnings growth reflected in investment decisions and the company's ability to generate profit as key indicators of its prospects. Simultaneously, all four variables continue to play a role in shaping investors' assessment of the value of conventional banking companies. In conclusion, investment decisions and profitability are more relevant fundamental factors than dividend policy and capital structure in determining firm value in the banking sector.